2022
DOI: 10.1007/s11157-022-09627-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective CO2 and CO bioconversion into ectoines using novel microbial platforms

Abstract: Microbial conversion of CO2 and CO into chemicals is a promising route that can contribute to the cost-effective reduction of anthropogenic green house and waste gas emissions and create a more circular economy. However, the biotechnological valorization of CO2 and CO into chemicals is still restricted by the limited number of model microorganisms implemented, and the small profit margin of the products synthesized. This perspective paper intends to explore the genetic potential for the microbial conversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, there has recently been an increase in research to improve and advance bacterial-based BioCon CO 2 technology. Both aerobic and anaerobic bacteria grew autotrophically on gas components and followed a specific pathway to produce fuels and chemicals from inorganic waste gases [82,83]. Closed and open photobioreactors were used as advanced biological technologies for BioCon CO 2 [84].…”
Section: Bacteria-based Biocon Co 2 Processesmentioning
confidence: 99%
“…However, there has recently been an increase in research to improve and advance bacterial-based BioCon CO 2 technology. Both aerobic and anaerobic bacteria grew autotrophically on gas components and followed a specific pathway to produce fuels and chemicals from inorganic waste gases [82,83]. Closed and open photobioreactors were used as advanced biological technologies for BioCon CO 2 [84].…”
Section: Bacteria-based Biocon Co 2 Processesmentioning
confidence: 99%
“…Therefore, carbon capture and utilization via conversion (CCU) has become an important strategy to mitigate CO 2 emissions and produce carbonbased chemicals and fuels. [2][3][4] Several methods have been proposed to convert CO 2 , including thermal, 5 chemical, 6 and bio-conversion 7 Developing IL-based CO 2 R has been conducted. It was found that, when ILs were immobilized into the cathode catalyst, the cell operating current was increased by a factor of two or more, and FE was enhanced by 20-30 %, indicating that ILs could effectively promote CO 2 R. 42 Rosen et al 50 were the first to report that the use of 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF 4 ]) increased the selectivity for CO and lowered the overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, carbon capture and utilization via conversion (CCU) have become an important strategy to mitigate CO 2 emissions and produce carbon-based chemicals and fuels. [2][3][4] Several methods have been proposed to convert CO 2 , including thermal, 5 chemical, 6 and bio-conversion 7 as well as electrocatalytic, [8][9][10] photocatalytic, 11 and photoelectric 12 conversions and coconversions. Among them, electrochemical CO 2 reduction (CO 2 R) is among the most promising owing to the mild reaction conditions, as well as easy and flexible controllability.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, halotolerant bacteria are known to accumulate compatible solutes, such as ectoine, hydroxyectoine, glycine betaine, and proline betaine, to counteract osmotic stresses. These compounds are commercially relevant because they have potential uses as moisturizers and protein stabilizers in the cosmetics and food industries ( Liu et al, 2019 ; Sekar and Kim, 2020 ; Cantera et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%